SEMANTIC NETWORK OF THE WORD ASSOCIATION IN THE FIELD OF LAW - Arti Prihatini (LITERA, 2019)
Word association can be utilized for identifying semantic network and describing point of view and prior knowledge of someone. This study aims to discuss two focuses, (1) the categorization of response word and (2) language factors that form semantic networks from the response words of word association in the field of law. This research uses a qualitative approach which is a type of descriptive case study research. Data collection held by using a word association questionaire. Based on the word categorization, the results showed that the stimulus words in the form of nouns were the most responded by nouns, verbs were the most responded by nouns, while the adjectives were responded more by an adjectives. Overall, responses in the form of nouns are 64.71%, verbs are 17.70%, adjectives are 17.58%. The responses in the form of nouns are related to the semantic relations of argument and predication, while the adjective response tends to be related to other adjectives in the unity of the semantic network. The response words form semantic network based on language factors, namely (1) lexical factors that consist of meaning relationship, connotation of meaning, concreteness and abstractness and (2) grammatical factors that consist of syntagmatic-paradigmatic and predication-argument relationship. Keywords: semantic network, word association, mental lexicon